To add the polynomial expressions \(2r^2 - 3r + 4\) and \(-2r^2 + 3r + 6\), we combine like terms.
-
Start with the expressions: \[ (2r^2 - 3r + 4) + (-2r^2 + 3r + 6) \]
-
Group the like terms: \[ (2r^2 - 2r^2) + (-3r + 3r) + (4 + 6) \]
-
Simplify each group:
- For the \(r^2\) terms: \(2r^2 - 2r^2 = 0\)
- For the \(r\) terms: \(-3r + 3r = 0\)
- For the constant terms: \(4 + 6 = 10\)
-
Combine the results: \[ 0 + 0 + 10 = 10 \]
Thus, the sum of the polynomials \(2r^2 - 3r + 4\) and \(-2r^2 + 3r + 6\) is \(10\).